2022
DOI: 10.3390/ijms23052514
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Two Neuronal Sigma-1 Receptor Modulators, PRE084 and DMT, on Neurogenesis and Neuroinflammation in an Aβ1–42-Injected, Wild-Type Mouse Model of AD

Abstract: Alzheimer’s disease (AD) is the most common form of dementia characterized by cognitive dysfunctions. Pharmacological interventions to slow the progression of AD are intensively studied. A potential direction targets neuronal sigma-1 receptors (S1Rs). S1R ligands are recognized as promising therapeutic agents that may alleviate symptom severity of AD, possibly via preventing amyloid-β-(Aβ-) induced neurotoxicity on the endoplasmic reticulum stress-associated pathways. Furthermore, S1Rs may also modulate adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 114 publications
1
12
0
Order By: Relevance
“…The oral LD 50 of DMT in mice was reported as 47 mg/kg intraperitoneally and 32 mg/kg intravenously. 49 A study conducted by Borbély and colleagues 50 investigated the neurogenic and anti-neuroinflammatory effects of DMT in a mouse model of Alzheimer's disease. DMT was intraperitoneally injected at a concentration of 1 mg/kg-1 into male C57BL/6 wild-type mice (n = 80), treated with either amyloid-β peptide 1-42-oligomers (polymer whose molecules consist of relatively few repeating units) or vehicle (phosphate-buffered saline [PBS]) as a control.…”
Section: Isolated Dmtmentioning
confidence: 99%
“…The oral LD 50 of DMT in mice was reported as 47 mg/kg intraperitoneally and 32 mg/kg intravenously. 49 A study conducted by Borbély and colleagues 50 investigated the neurogenic and anti-neuroinflammatory effects of DMT in a mouse model of Alzheimer's disease. DMT was intraperitoneally injected at a concentration of 1 mg/kg-1 into male C57BL/6 wild-type mice (n = 80), treated with either amyloid-β peptide 1-42-oligomers (polymer whose molecules consist of relatively few repeating units) or vehicle (phosphate-buffered saline [PBS]) as a control.…”
Section: Isolated Dmtmentioning
confidence: 99%
“…It is thought that this damage in the hippocampus can occur up to 10 years before cognitive symptoms appear in the patient. Studies using Aβ 1–42 [ 391 ] or Aβ 25–35 [ 392 ] injections into mouse brains have shown reduced proliferation and neurite growth, increased death of newly formed cells and an increase in the number of immature cells in mice brains. PRE-084 treatment promotes neurogenesis in mice treated with Aβ 1–42 or Aβ 25–35 [ 391 , 392 ].…”
Section: Sigma Receptor Ligands For Neurological Diseasementioning
confidence: 99%
“…Studies using Aβ 1–42 [ 391 ] or Aβ 25–35 [ 392 ] injections into mouse brains have shown reduced proliferation and neurite growth, increased death of newly formed cells and an increase in the number of immature cells in mice brains. PRE-084 treatment promotes neurogenesis in mice treated with Aβ 1–42 or Aβ 25–35 [ 391 , 392 ]. Furthermore, the density of hyper-reactive astrocytes was reduced by the administration of PRE-084 [ 391 ], suggesting PRE-084 may play an anti-inflammatory role.…”
Section: Sigma Receptor Ligands For Neurological Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…PSEN1 FAD mutation knock-in mice show impaired adult neurogenesis associated with cognitive dysfunction and NPS status [100]. An increase in adult neurogenesis contributes to the improvement of cognitive dysfunction in AD model mice [101][102][103][104]. Therefore, adult neurogenesis in the hippocampus is an important target for AD therapy [105].…”
Section: Nerve Regeneration In Patients With Admentioning
confidence: 99%